2015
DOI: 10.1111/dom.12587
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐directional interaction between hypoglycaemia and cognitive impairment in elderly patients treated with glucose‐lowering agents: a systematic review and meta‐analysis

Abstract: Aims: Recent research suggests the possibility of a bi-directional relationship whereby hypoglycaemia is a risk factor for dementia, and also where dementia increases risk of hypoglycaemia. We aimed to examine this relationship in older patients with diabetes mellitus treated with glucose lowering agents. Materials and Methods:We searched MEDLINE and EMBASE over a ten year span 2005 to 2015 (with automated PubMed updates to August 2015) for observational studies of the association between hypoglycaemia and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 31 publications
2
71
0
6
Order By: Relevance
“…Hypoglycemia is a clinically important ADR, especially among elderly patients, that may limit attempts to achieve tight glycemic control or might increase the risk of other severe outcomes, especially in elderly patients [14][15][16][17]. In the present study, we noted that low BMI (<18.5 kg/m 2 ) and the use of insulin were potential risk factors for hypoglycemia.…”
Section: Risk Factors For Adrsmentioning
confidence: 49%
“…Hypoglycemia is a clinically important ADR, especially among elderly patients, that may limit attempts to achieve tight glycemic control or might increase the risk of other severe outcomes, especially in elderly patients [14][15][16][17]. In the present study, we noted that low BMI (<18.5 kg/m 2 ) and the use of insulin were potential risk factors for hypoglycemia.…”
Section: Risk Factors For Adrsmentioning
confidence: 49%
“…Hambling and colleagues observed that older people, including those with comorbidities such as CKD or dementia, were managed to similar intensive thresholds as those without CKD or dementia . These older patients are especially vulnerable to hypoglycaemic episodes and other adverse events such as fractures, head injuries, CVD, or even death, given predisposing factors such as advanced age, frailty, long duration of diabetes, polypharmacy, and comorbidities such as CKD and cognitive impairment . Intensive treatment with antihyperglycaemic medication in these patients doubles the risk of hypoglycaemia .…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of hypoglycaemia impact substantially on patients and the healthcare system: these include physical injury, psychological harm, impaired cognition, reduced quality of life, mortality, additional manpower and resource utilization, and the costs of providing emergency assistance . The majority of older type 2 diabetes patients have coexisting frailty and comorbidities such as renal and cognitive impairment, and the risk of hypoglycaemia is particularly high in these patients . Despite recommendations by guideline bodies to individualize glycaemic targets with risk assessments aimed at avoiding overtreatment and hypogycaemia, recent data suggest increased hospital emergencies for hypoglycaemia .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving older individuals with diabetes have identified potentially serious consequences (eg, cardiovascular events, falls, fractures and death) that extend beyond the acute event of hypoglycaemia . However, most of the studies have not specifically focused on these hypoglycaemia‐related complications in older individuals with dementia, although there is evidence from a recent meta‐analysis that patients with diabetes and dementia may be even more prone to hypoglycaemia and subsequent cognitive complications …”
Section: Introductionmentioning
confidence: 99%